Menstrual health status and cultural practices of tribal adolescent girls - D., Sridhar; N., Gauthami (International Journal Of Community Medicine And Public Health, 2017)
Background: Adolescence in the life cycle of a Homosapien organism is a period of transition from childhood to adulthood. The word ‘Adolescent’ has been derived from Latin word ‘Adolescere’ which means ‘to grow to maturity’. The children from the poor scheduled tribes families are not being sent to school because of the tendency of some parents to utilize their services in augmenting their family income. Therefore a provision for educational opportunities forms a very important part of the programme for the welfare of the scheduled tribes. The aim of the present study was to observe menstrual health of the tribal adolescent girls and to describe cultural factors on study population. Methods: Community based cross sectional descriptive study done on 425 tribal adolescent girls residing in 18 habitations of Achampet mandal. Pre designed pre tested semi structured schedule applied on the subjects after a written informed consent. Results: Out of 425 study subjects majority 178 (41.9%) were from early adolescent age i.e. 10-13 years, followed by 144 (33.9%) from mid adolescent age i.e., 14-15 years and 103 (24.2%) from late adolescent age i.e. 16-19 years. Majority illiterate subjects (55.1%) menstrual hygiene was non sanitary. Subjects who had illiterate mothers their menstrual hygiene was non sanitary way (55.1%). Girls in joint families were having sanitary menstrual hygiene. Conclusions: Present study showed education and awareness play key role in maintaining menstrual hygiene. Hygiene education is supposed to be given at all levels. Bad cultural practices supposed be addressed at community level with intervention.